Propozycja nowego algorytmu wyznaczającego liczbę skupień - Korzeniewski, Jerzy (Proposal of New Algorithm for Determining the Number of Clusters, 2005)
The new algorithm is based on the comparison of pseudo cumulative distribution functions of a certain random variable. This variable is defined as follows. For a fixed window size we draw k different points and for every point we find the corresponding limiting point in the mean shift procedure. Then we check if the distance (e.g. Euclidean) between every pair of the limiting points is smaller than the window size. The probability of meeting this condition is the value of the pseudo cumulative distribution function at the point equal to the window size. Analogously we determine the pseudo cumulative distribution functions for different numbers k of clusters. The proper number of clusters is the one that corresponds to the last (with respect to k) curve to possess a horizontal phase at the altitude smaller than 1.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (12); 2005; nr 1076, s. 257-264